Colonialism, the Cold War Era, and Marginal Space: The Existential Conditions of Four Decades of Hong Kong Literature - Tay, William (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
Besides proposing various possible reasons for the non-existence of a literature in English from the British Crown Colony of Hong Kong, this paper tries to explain how the Cold War and the ideological struggles between the Nationalists and the Communists allowed and promoted the growth of literary writings in Chinese. But very often these works tended to speak to the centers (China or Taiwan) from the marginal space of Hong Kong.